"Psalmen in den Nacht": 200 jaar van kerkliedere geskep en gesing in die Kaap van Storms en die Kaap de Goede Hoop = "Psalmen in den Nacht": 200 Years of Church Hymns created and sung in the Cape of Storms and the Cape of Good Hope - Murray, Isabel (Stellenbosch theological journal, 2024)
Jan van Riebeeck brought the Genevan Psalms with him to the Cape, setting the scene for the DRC’s church music development. By 1824, various faith groups have congregated in the Cape Colony, each introducing their religious music and practices. For the next two hundred years the officials connected to the Cape Synod would diligently collect and store the thousands of documents, hymnbooks, even musical instruments and technology relating the story of the DRC’s church music. In 2024 a comprehensive process of establishing an inclusive DRC Church Music Collection has been launched, requiring a re-focus to acknowledge influences and contributions from people and sources. This article highlights a few of the more unexpected findings, such as the contributions made by the fictional "Oom Willem Smit"; the "pastor of the Richtersveld", Eerwaarde JF Hein; "ziekentrooster" Mother Machteldt Smit of the Cape and the revival singer Ira D Sankey and ABW-prisoner Willie Louw. Lastly, a few examples are given of the DRC’s pioneer missionaries’ influence on African indigenous music, such as the Chechewa Hymnbook.